2021
DOI: 10.1021/jacs.1c09274
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Electronic Insights into a Working NiAu Single-Atom Alloy Ethanol Dehydrogenation Catalyst

Abstract: Elucidation of reaction mechanisms and the geometric and electronic structure of the active sites themselves is a challenging, yet essential task in the design of new heterogeneous catalysts. Such investigations are best implemented via a multi-pronged approach that comprises ambient pressure catalysis, surface science, and theory. Herein, we employ this strategy to understand the workings of NiAu single-atom alloy (SAA) catalysts for the selective non-oxidative dehydrogenation of ethanol to acetaldehyde and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 75 publications
2
46
0
Order By: Relevance
“… 32 37 There are examples in the literature where charge analyses on DFT calculations were performed to explain experimental shifts observed in X-ray absorption and photoemission spectra. 38 , 39 However, the origin of these charges on the dopant atom and their impact on the stability of chemical intermediates adsorbed on the dopant site of SAAs (electrostatic repulsion/attraction) are yet to be understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 32 37 There are examples in the literature where charge analyses on DFT calculations were performed to explain experimental shifts observed in X-ray absorption and photoemission spectra. 38 , 39 However, the origin of these charges on the dopant atom and their impact on the stability of chemical intermediates adsorbed on the dopant site of SAAs (electrostatic repulsion/attraction) are yet to be understood.…”
mentioning
confidence: 99%
“…On PtCu ( q d = −0.61 e ), the O–H cleavage is reported to be the first elementary step, 46 whereas on NiAu ( q d = +0.32 e ), the C–H cleavage occurs first. 39 …”
mentioning
confidence: 99%
“…9,10 At present, the common carriers to anchor single metal atoms include metal oxides, 11 transition metal sulfides (TMDs), 12 MXenes, 13 carbon materials, 14 and alloys. 15,16 Among them, the carbon support has a large specific surface area, good electrical conductivity, high porosity, outstanding chemical stability and corrosion resistance, and low cost, making it the most used substrate for SACs. 17–19 In 1964, Jasinski successfully prepared a cobalt phthalocyanine catalyst with Co–N 4 coordination, and found that it can catalyze the ORR under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom alloys (SAAs) are a type of single-atom catalyst consisting of a somewhat inert host metal doped with single atoms of a more reactive metal. Unlike most catalysts, single-atom alloys were discovered by using fundamental microscopy and desorption measurements on single crystals under model-system ultra-high vacuum (UHV) conditions before making the transition to nanoparticle analogues. Since these initial studies, close synergy between model-system work under UHV and nanoparticle studies under industrially relevant conditions has enabled the design and understanding of these materials.…”
mentioning
confidence: 99%